Besedni red, usvajanje prvega in učenje drugega/tujega jezika - Kranjc, Simona (Jezik in slovstvo, 2004)
In the first part of the article the author discusses the typical features of learning a foreign language and the factors that influence thisž The process is compared to the process of first language acquisition with the conclusion that learning a foreign language, and first language acquisition are quite similar, although they differ considelably in some points, in paticular, as far as the students' cognitive ability is concerned, if those learning a foreign languge are not children. The second part of the article discusses the question of word order and its treatment in literature, concluding that teaching word order is a very important component of teaching Slovene as a foreign language.
Keywords: jezikovni pouk; slovenščina kot drugi ali tuji jezik; materinščina; first language; skladnja; syntax; besedni red